Activation, mental toughness, and psychological wellbeing in water sports - Trujillo Santana, Tomás; López-Morales, José Luis; Romero, Areli Benitex; Peinado Portero, Ana I.; López Fajardo, Adriana Daniela; Baidez, Miryam Maestre (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
A non-optimal level of activation for the specific competitive moment negatively affects the athlete’s performance, while an adequate level of activation can promote positive feelings, cognitions, and behaviors that contribute to the athlete’s mental toughness and, in turn, to psychological wellbeing. The aim of this study was to assess the levels of activation and mental toughness subscales among adolescent and young adult athletes with high performance in water sports. The results indicate that athletes with high mental toughness scores also obtained higher scores on the activation subscale, and those with high mental toughness showed higher psychological wellbeing in this study. Therefore, it seems important to develop intervention programs for young athletes aimed at enhancing the skills related to the variables studied.